Anabolic steroids in sport and exercise - Yesalis, Charles (Human Kinetics, 2000)
This text presents research findings on the use and abuse of steroids in sports and exercise, and information on steroid use within professional sports and among Olympic athletes. In addition, information on drug use among international student athletes, adolescents and body builders is explored.